2019
DOI: 10.1161/atvbaha.119.312787
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vascular Smooth Muscle Cell Phenotypic Switching and Calcification in Aortic Aneurysm Formation

Abstract: Aortic aneurysm is a vascular disease whereby the ECM (extracellular matrix) of a blood vessel degenerates, leading to dilation and eventually vessel wall rupture. Recently, it was shown that calcification of the vessel wall is involved in both the initiation and progression of aneurysms. Changes in aortic wall structure that lead to aneurysm formation and vascular calcification are actively mediated by vascular smooth muscle cells. Vascular smooth muscle cells in a healthy vessel wall are termed contractile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
186
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(212 citation statements)
references
References 264 publications
2
186
0
2
Order By: Relevance
“…Examination of early cultures (passage 1-3) by light microscopy demonstrated that VSMC derived from Aim2-/mice reproducibly formed large rhomboidal cells with star-shaped laments ( Figure 1a), as described for the synthetic phenotype (reviewed in (Petsophonsakul et al, 2019)). In contrast, VSMC derived from WT mice were spindle-shaped and grew densely packed in typical hills and valleys as described for the contractile phenotype (Petsophonsakul et al, 2019). Furthermore, VSMC derived from Aim2-/mice grew slowly with an average doubling time of 3-4 days and reached senescence after 8.3 +/-2.3 passages (1:2 splitting), whereas VSMC derived from WT mice stopped growing after 11.3 +/-1.1 passages (Figure 1b).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Examination of early cultures (passage 1-3) by light microscopy demonstrated that VSMC derived from Aim2-/mice reproducibly formed large rhomboidal cells with star-shaped laments ( Figure 1a), as described for the synthetic phenotype (reviewed in (Petsophonsakul et al, 2019)). In contrast, VSMC derived from WT mice were spindle-shaped and grew densely packed in typical hills and valleys as described for the contractile phenotype (Petsophonsakul et al, 2019). Furthermore, VSMC derived from Aim2-/mice grew slowly with an average doubling time of 3-4 days and reached senescence after 8.3 +/-2.3 passages (1:2 splitting), whereas VSMC derived from WT mice stopped growing after 11.3 +/-1.1 passages (Figure 1b).…”
Section: Resultsmentioning
confidence: 65%
“…Because VSMC phenotypic switching and calci cation were shown to be a key event in aneurysm formation (Petsophonsakul et al, 2019), we next asked whether AIM2 is involved in VSMC calci cation. To address this query, proliferating and senescent VSMC were shifted to mineralization medium for two weeks in vitro.…”
Section: Aim2 Knockout Promotes Osteoblastogenic Differentiation Of Mmentioning
confidence: 99%
“…In addition to increasing MMP expression, the activation of ERK1/2 signaling pathways through redox-related events can disrupt aortic wall homeostasis by altering the characteristics of VSMCs. Activation of ERK1/2 in the presence of both 3-nitrotyrosine and 3-chlorotyrosine, markers of MPO-mediated oxidative damage, has been shown to promote human aortic VSMC migration [ 138 , 139 ], consistent with the pathological synthetic phenotype associated with TAA pathogenesis [ 140 ]. Nitrotyrosine levels have been shown to be increased in the aortic medial layer of both aggressive forms of human TAA [ 141 ] and human TAA tissue and cultured smooth muscle cells from MFS patients [ 141 , 142 ].…”
Section: Mpo-associated Oxidative Stress and Links To Taa Pathogenmentioning
confidence: 99%
“…With all this strong evidence in place, we speculate that the TGF-β pathway might play a relevant role, inducing angiogenic factors that contribute to ECM degradation within the PA. An alteration of this pathway might therefore contribute to damage of the vessel wall (including fibroblasts, smooth muscle, and endothelial cells), already subjected to high afterload and therefore contributing to dilation and aneurysm. In addition, it will be interesting to further explore if an aberrant SMC phenotypic switching that is able to induce excessive proliferation and metalloproteinase production that degrades the ECM and increased extracellular vesicles secretion that promotes vascular inflammation and calcification (such as in the TAA [94]), might have a role in the development of PAA. Since PAH is usually diagnosed at advanced stages, with established non-reversible tissue changes, by the time pulmonary vasodilator therapy is started, the PA wall is already damaged.…”
Section: Future Trends For Research and Patient Carementioning
confidence: 99%